Novel Stereoselective High‐Performance Liquid Chromatographic Method for Simultaneous Determination of Guaifenesin and Ketorolac Enantiomers in Human Plasma. Issue 10 (8th July 2014) - Maher, Hadir M.; Al‐Taweel, Shorog M.; Alshehri, Mona M.; Alzoman, Nourah Z.
ABSTRACT A novel method was developed for the simultaneous determination of guaifenesin (GUA) and ketorolac tromethamine (KET) enantiomers in plasma samples. Since GUA probably increases the absorption of coadministered drugs (e.g., KET), it would be extremely important to monitor KET plasma levels for the purpose of dose adjustment with a subsequent decrease in the side effects. Enantiomeric resolution was achieved on a polysaccharide‐based chiral stationary phase, amylose‐2, as a chiral selector under the normal phase (NP) mode and using ornidazole (ORN) as internal standard. This innovative method has the advantage of the ease and reliability of sample preparation for plasma samples. Sample clean‐up was based on simply using methanol for protein precipitation followed by direct extraction of drug residues using ethanol. Both GUA and KET enantiomers were separated using an isocratic mobile phase composed of hexane/isopropanol/trifluoroacetic acid, 85:15:0.05 v/v/v. Peak area ratios were linear over the range 0.05–20 µg/mL for the four enantiomers S (+) GUA, R (–) GUA, R (+) KET, and S (–) KET. The method was fully validated according to the International Conference on Harmonization (ICH) guidelines in terms of system suitability, specificity, accuracy, precision, robustness, and solution stability. Finally, this procedure was innovative to apply the rationale of developing a chiral high‐performance liquid chromatography (HPLC) procedure for the simultaneous quantitative analysis of drug isomers in clinical samples. Chirality 26:629–639, 2014. © 2014 Wiley Periodicals, Inc.